Solar cell gel electrolyte and preparation method thereof

By preparing modified composite nanomaterials and cellulose-based polyurethane, combining sulfonate ions and naphthalene diimide conjugated units, the defects of liquid and solid electrolytes are solved, and the conductivity and stability of solar cell gel electrolytes are improved. Improve the photoelectric conversion efficiency of dye-sensitized solar cells.

CN119208023AInactive Publication Date: 2024-12-27WUHAN OSBER OPTOELECTRONICS TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411460712.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Liquid electrolytes have problems with solvent volatility and solution leakage, while solid electrolytes have problems with low conductivity and poor interface compatibility, which affects the stability and photoelectric conversion efficiency of dye-sensitized solar cells.

Method used

Using a preparation method of solar cell gel electrolyte, composite metal oxides are prepared by using tin chloride pentahydrate and copper sulfate pentahydrate as metal precursors, and MXene powder is formed with Ti3AlC2 powder, and through γ-aminopropyl triethyl The reaction of oxysilane and 3,4-dihydroxyphenylacetic acid can obtain modified composite nanomaterials, combined with NaI and iodine, and used modified microcrystalline cellulose and quaternary ammonium compounds to form cellulose-based polyurethane, and introduced Sulfonate ionic groups and naphthalene diimide conjugated units improve conductivity and structural stability.

Benefits of technology

Solved the problems of solvent volatility of liquid electrolytes and low conductivity of solid electrolytes, improve the conductivity and stability of gel electrolytes, enhance the photoelectric conversion efficiency and interface compatibility of solar cells, and achieve more efficient electrochemical performance. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208023A_ABST
    Figure CN119208023A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of solar cells, and discloses a solar cell gel electrolyte and a preparation method thereof. The preparation method of the solar cell gel electrolyte comprises the following steps: firstly preparing a composite metal oxide, and then preparing MXene powder; the MXene powder and the composite metal oxide are compounded to obtain a composite nano material; treating the composite nano material with gamma-aminopropyltriethoxysilane, and then sequentially reacting with 3, 4-dihydroxyphenylacetic acid and 1, 3-propane sultone, so as to obtain a composite modifier; preparing modified microcrystalline cellulose; mixing NaI and elemental iodine, and then adding a solvent to obtain an electrolyte; modified microcrystalline cellulose, a quaternary ammonium salt compound, toluene diisocynate and a composite modifier are used as raw materials to react and then are mixed with an electrolyte, and the solar cell gel electrolyte is prepared. The solar cell gel electrolyte has good conductivity and flexibility, and the photoelectric conversion efficiency of a solar cell can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solar cells, in particular to a solar cell gel electrolyte and a preparation method thereof. Background Art

[0002] Solar cells mainly include silicon-based solar cells, multi-compound thin-film solar cells, organic solar cells, dye-sensitized solar cells and perovskite solar cells. Among them, dye-sensitized solar cells (DSSC) have the advantages of low cost, easy processing and no pollution. They can be used for building exterior walls, electronic products, fabric power generation, etc., and have broad application prospects. Dye-sensitized solar cells are composed of photoanode, sensitizing dye, electrolyte and counter electrode. Among them, electrolyte is the medium for charge transfer between photoanode and counter electrode, and is a link in the formation of photochemical cycle. Its performance directly affects the photoelectric conversion efficiency of the battery.

[0003] For example, Chinese patent CN101436467B discloses an ionic liquid electrolyte containing bis(fluorosulfonyl)imide ionic liquid and iodide ions and its application, which is a composition obtained by uniformly mixing an ionic liquid containing bis(fluorosulfonyl)imide ionic liquid, iodide ions and elemental iodine according to a proportion; or, it is a composition obtained by uniformly mixing an ionic liquid containing bis(fluorosulfonyl)imide ionic liquid, iodide ions and elemental iodine; and one or more of other ionic liquids, additives, curing agents and solvents according to a proportion; the ionic liquid electrolyte containing bis(fluorosulfonyl)imide ionic liquid and iodide ions is applied to dye-sensitized solar cells to obtain a high-efficiency thermally stable device with a photoelectric power conversion efficiency of 7.5%;

[0004] Another example is Chinese patent CN109545562B which discloses a solid electrolyte for dye-sensitized solar cells, characterized in that it comprises the following components in parts by weight: 35-55 parts of tetraacetonitrile quaternary ammonium salt type ionic crystals; 10-15 parts of 3,6-diethynylcarbazole organic ions; 5-10 parts of iodine; 5-8 parts of additives; 2-5 parts of surface ionized modified graphene quantum dots; the additives are one or more of methylbenzimidazole, butylbenzimidazole, and tert-butylpyridine. The solid electrolyte for dye-sensitized solar cells has the advantages of low preparation cost, higher conductivity, better stability, easier packaging, and can effectively improve the stability and photoelectric conversion efficiency of dye-sensitized solar cells, and is safer and more environmentally friendly to use;

[0005] However, liquid electrolytes have problems such as solvent volatilization and solution leakage, while solid electrolytes have problems such as low conductivity and poor interface compatibility. Summary of the invention

[0006] In order to solve the above technical problems, the present invention provides a method for preparing a solar cell gel electrolyte, comprising the following steps:

[0007] Step (1), using tin chloride pentahydrate and copper sulfate pentahydrate as metal precursors to prepare a composite metal oxide;

[0008] Step (2), using MAX phase Ti 3 AlC 2 The powder is used as a raw material to prepare MXene powder; the MXene powder and the composite metal oxide are combined to obtain a composite nanomaterial;

[0009] Step (3), the composite nanomaterial is treated with γ-aminopropyltriethoxysilane to obtain a surface-modified composite nanomaterial; the surface-modified composite nanomaterial is reacted with 3,4-dihydroxyphenylacetic acid to obtain a modified composite nanomaterial; the modified composite nanomaterial is reacted with 1,3-propane sultone to obtain a composite modifier;

[0010] Step (4), the pretreated microcrystalline cellulose is modified by naphthalene diimide-N,N'-diacetic acid to obtain modified microcrystalline cellulose;

[0011] Step (5), NaI and iodine are mixed, and 1,4-butyrolactone is used as a solvent to obtain an electrolyte; modified microcrystalline cellulose, quaternary ammonium salt compound, toluene diisocyanate, and a composite modifier are reacted as raw materials, and then mixed with the electrolyte to prepare a solar cell gel electrolyte;

[0012] Wherein, the preparation method of the quaternary ammonium salt compound comprises the following steps:

[0013] Step S1, lauric acid reacts with glycidoxypropyl-terminated polydimethylsiloxane to obtain an intermediate product A;

[0014] Step S2, reacting the intermediate product A with tris(3-aminopropyl)amine to obtain an intermediate product B;

[0015] Step S3, using the intermediate product B and iodopropane as raw materials to prepare a quaternary ammonium salt compound.

[0016] Preferably, in the step (1), the preparation method of the composite metal oxide is as follows: tin chloride pentahydrate and copper sulfate pentahydrate are added to deionized water to form a mixed salt solution, wherein the content of tin ions and copper ions in the mixed salt solution is 40-50wt%, and a sodium hydroxide aqueous solution with a concentration of 1-2 mol / L is added dropwise to the mixed salt solution at a rate of 0.5-1.5 mL / min under the stirring condition of 150-250 r / min at 20-40° C., the temperature is raised to 120-140° C. and the reaction is maintained for 15-25 h, filtered, washed, and the composite metal oxide is obtained, wherein the volume ratio of the mixed salt solution to the sodium hydroxide aqueous solution is 1:(0.5-2);

[0017] In the above process, tin chloride pentahydrate and copper sulfate pentahydrate are used as precursors to prepare a composite metal oxide composed of copper oxide and tin oxide;

[0018] Preferably, in step (2), the preparation method of the composite nanomaterial is:

[0019] At room temperature, the MAX phase of Ti 3 AlC 2 The powder is added to 48wt% hydrofluoric acid within 10-20min, stirred for 20-40min, and then stirred in an oil bath at 40-60°C for 12-15h. After the reaction is completed, centrifuge, and the obtained precipitate is washed with deionized water until the pH of the washing liquid is 5-6, and then dried at 60-100°C for 10-16h to obtain MXene powder; wherein, the Ti of the MAX phase 3 AlC 2 The ratio of powder to hydrofluoric acid is (2-4) g: (40-100) mL;

[0020] Add the composite metal oxide to deionized water, stir for 1.5-2.5 hours, then add MXene powder, ultrasonically treat for 30-60 minutes, filter, and heat the obtained solid product at 100-120° C. for 8-12 hours to obtain a composite nanomaterial, wherein the mass ratio of the composite metal oxide, MXene powder and deionized water is (0.2-0.6):1:(50-100);

[0021] In the above process, the MAX phase Ti 3 AlC 2 The powder is used as a raw material to obtain a MXene powder with a nano-sheet microstructure, and then a composite metal oxide is deposited on the MXene nanosheet to obtain a composite nanomaterial hybridized with copper oxide, tin oxide and MXene;

[0022] Preferably, in the step (3), the preparation method of the surface-modified composite nanomaterial is as follows: adding γ-aminopropyltriethoxysilane to an ethanol aqueous solution with a volume fraction of 90%, adjusting the pH to 3-4 with an acetic acid aqueous solution with a concentration of 0.1 mol / L, and then adding the composite nanomaterial, stirring and reacting at 60-70°C and a speed of 400-600 r / min for 20-40 min, filtering, washing, and drying to obtain the surface-modified composite nanomaterial; wherein the mass ratio of γ-aminopropyltriethoxysilane, ethanol aqueous solution, and composite nanomaterial is (0.1-0.4):(8-10):(2-5);

[0023] In the above process, the composite nanomaterial is surface treated by γ-aminopropyltriethoxysilane to introduce amino groups on the surface of the composite nanomaterial;

[0024] Preferably, in the step (3), the preparation method of the modified composite nanomaterial is as follows: 3,4-dihydroxyphenylacetic acid is dissolved in N,N-dimethylformamide, 1,3-dicyclohexylcarbodiimide and N-hydroxysuccinimide are added, and the mixture is stirred for 2-3 hours. The surface-modified composite nanomaterial is added under stirring, the pH value is adjusted to 5.4-5.6 with a 1 mol / L hydrochloric acid aqueous solution, and the mixture is reacted in nitrogen for 20-30 hours. The mixture is filtered, washed with methanol, and dried to obtain the modified composite nanomaterial. The mass ratio of 3,4-dihydroxyphenylacetic acid, N,N-dimethylformamide, 1,3-dicyclohexylcarbodiimide, N-hydroxysuccinimide, and the surface-modified composite nanomaterial is (1.5-3):(80-120):(1.8-3.7):(1.1-2.2):(2-4);

[0025] In the above process, the amino groups on the surface of the surface-modified composite nanomaterial react with the carboxyl groups of 3,4-dihydroxyphenylacetic acid to undergo an amidation reaction, thereby introducing amide groups on the surface of the modified composite nanomaterial;

[0026] Preferably, in step (3), the preparation method of the composite modifier is as follows: dimethyl sulfoxide and sodium hydride are mixed, nitrogen is passed through, and the mixture is stirred at 20-25°C for 20-40 minutes, then the mixture is heated to 70-80°C and stirred until the sodium hydride is completely dissolved, the mixture is cooled to room temperature, the modified composite nanomaterial is added, the mixture is stirred at 28-33°C for 20-40 minutes, 1,3-propane sultone is added, the reaction is continued by stirring for 4-10 hours, the mixture is filtered, washed, and dried to obtain the composite modifier; wherein the mass ratio of dimethyl sulfoxide, sodium hydride, modified composite nanomaterial, and 1,3-propane sultone is (300-500):(0.7-0.8):(4.8-7.4):(2.9-5);

[0027] In the above process, under the action of sodium hydride, the active hydrogen in the amide group of the modified composite nanomaterial reacts with 1,3-propane sultone, and a sulfonate ion group is introduced on the surface of the composite modifier to obtain a composite modifier;

[0028] Preferably, in step (4), the preparation method of the modified microcrystalline cellulose comprises: mixing microcrystalline cellulose and N,N-dimethylacetamide in a mass ratio of (10-20):(200-300), ultrasonicating for 1-2 hours, cooling and precipitating, washing, and drying to obtain pretreated microcrystalline cellulose;

[0029] In the above process, the pretreated microcrystalline cellulose becomes swollen, the surface is damaged, cracks and tears appear, the specific surface area increases, and more free hydroxyl groups are exposed, thereby increasing the solubility and reactivity of the microcrystalline cellulose;

[0030] The pretreated microcrystalline cellulose and p-toluenesulfonic acid are added to an acetone dispersion of 5-10 wt% naphthalene diimide-N, N'-diacetic acid, and the mixture is reacted at 120-150° C. for 4-8 hours. After the reaction is completed, the mixture is centrifuged, washed, and dried to obtain modified microcrystalline cellulose; wherein the mass ratio of the pretreated microcrystalline cellulose, p-toluenesulfonic acid, and the acetone dispersion of naphthalene diimide-N, N'-diacetic acid is (10-15):(0.1-0.3):(100-200);

[0031] In the above process, under the catalytic action of p-toluenesulfonic acid, the hydroxyl groups on the surface of the pretreated microcrystalline cellulose react with the carboxyl groups of naphthalene diimide-N,N'-diacetic acid to introduce naphthalene diimide conjugated units into the microcrystalline cellulose;

[0032] Preferably, in the step (5), the preparation method of the solar cell gel electrolyte is as follows: NaI and iodine are mixed under light-proof conditions, the volume is fixed with a solvent 1,4-butyrolactone, and after ultrasonic treatment for 2-3 hours, the electrolyte is sealed and stored in a dark place to obtain an electrolyte; wherein the concentration of NaI in the electrolyte is 0.2-0.8 mol / L, and the concentration of iodine is 0.02-0.08 mol / L;

[0033] Use 1-propyl-3-methylimidazolium iodide as solvent, dehydrate for 1-3 hours at a temperature of 100-120°C and a vacuum pressure of 0.11-0.13KPa, then add modified microcrystalline cellulose and quaternary ammonium salt compounds under nitrogen protection, stir for 2.5-3.5 hours, cool to 50-55°C, add toluene diisocyanate, add electrolyte when the reactant becomes viscous, stir for 20-30 minutes, heat to 60-65°C, add composite modifier, stir for 10-20 minutes, and then add The electrolyte is heated to 75-80°C and reacted for 4-5 hours, and the reaction product is placed in a 70-80°C oven until it is in a gel state to obtain a solar cell gel electrolyte; wherein the mass ratio of 1-propyl-3-methylimidazole iodide, modified microcrystalline cellulose, quaternary ammonium salt compound, toluene diisocyanate, composite modifier, and electrolyte is (50-100):(2.5-5):(1.5-3.5):(10.1-20.2):(0.3-1):(69.5-146.4);

[0034] In the above process, modified microcrystalline cellulose, quaternary ammonium salt compound, toluene diisocyanate, and composite modifier are used as raw materials to react to obtain cellulose-based polyurethane, which is then mixed with an electrolyte to prepare a solar cell gel electrolyte;

[0035] Furthermore, in the step (5), the method for preparing the quaternary ammonium salt compound comprises the following steps:

[0036] Step S1, mixing lauric acid, acetone and tetrabutylammonium bromide, ultrasonically treating for 20-40 minutes, then dropping glycidoxypropyl-terminated polydimethylsiloxane at a rate of 0.5-1.5 mL / min, heating to reflux, stirring and reacting for 2-3 hours, filtering, washing and drying after the reaction to obtain an intermediate product A; wherein the mass ratio of lauric acid, acetone, tetrabutylammonium bromide and glycidoxypropyl-terminated polydimethylsiloxane is (2-4):(70-100):(0.05-0.1):(8-16);

[0037] In the above process, tetrabutylammonium bromide is used as a catalyst, and the epoxy group at one end of the glycidoxypropyl-terminated polydimethylsiloxane is ring-opened and reacts with the carboxyl group of lauric acid to obtain an intermediate product A containing a flexible siloxane long chain and a hydroxyl group;

[0038] Step S2, adding the intermediate product A to toluene, stirring for 20-40 minutes, then adding tri(3-aminopropyl)amine, stirring at 70-90° C. and at a speed of 150-250 r / min for 20-30 hours, after the reaction is completed, removing the solvent by vacuum rotary evaporation at 60-80° C., washing, and drying to obtain an intermediate product B; wherein the mass ratio of the intermediate product A, toluene, and tri(3-aminopropyl)amine is (3-6):(50-80):(2-4);

[0039] In the above process, the epoxy group at the other end of the intermediate product A is ring-opened and reacts with the amino group of tris(3-aminopropyl)amine to obtain the intermediate product B;

[0040] Step S3, in a nitrogen atmosphere, mixing iodopropane and the intermediate product B at 0-3° C. for 40-80 min, and then stirring at 50-70° C. at a speed of 150-250 r / min for 20-30 h, precipitating the resulting product in ether for 24-48 h, filtering, and drying to obtain a quaternary ammonium salt compound; wherein the mass ratio of iodopropane to the intermediate product B is (1.5-3.5):(5-10);

[0041] In the above process, iodopropane reacts with the intermediate product B to undergo a quaternization reaction to obtain a quaternary ammonium salt compound containing a flexible siloxane long chain, a hydroxyl group, and an iodide ion.

[0042] The solar cell gel electrolyte is prepared by the method for preparing the solar cell gel electrolyte.

[0043] Compared with the prior art, the present invention has the following beneficial effects:

[0044] 1. The natural polymer microcrystalline cellulose is used as the raw material, which is pretreated and modified, and then reacted with other substances such as bio-based quaternary ammonium salt compounds to obtain the solar cell gel electrolyte. The use of bio-based materials is more energy-saving and environmentally friendly. The gel electrolyte not only solves the problems of solvent volatilization and solution leakage in liquid electrolytes, but also solves the problems of low conductivity and poor interface compatibility of solid electrolytes.

[0045] 2. The present invention uses bio-based carboxylic acid lauric acid as a raw material, reacts with glycidoxypropyl-terminated polydimethylsiloxane and tri(3-aminopropyl)amine in sequence, and then reacts with iodopropane to obtain a bio-based quaternary ammonium salt compound, and introduces the bio-based quaternary ammonium salt compound into cellulose-based polyurethane. The introduction of the quaternary ammonium salt ion structure improves the conductivity of the gel electrolyte by enhancing the ion transmission capacity; the flexible siloxane long chain reduces the crystallinity of the cellulose-based polyurethane molecular chain, improves its ion transmission efficiency, and enhances the flexibility and entanglement of the cellulose-based polyurethane molecular chain, and improves the ability to absorb and retain electrolyte, thereby improving the performance of the gel electrolyte, and the enhanced flexibility of the cellulose-based polyurethane enables the solar cell gel electrolyte to better infiltrate the photoanode, thereby reducing the interface contact resistance of the solar cell.

[0046] 3. The present invention uses natural polymer microcrystalline cellulose as raw material, introduces naphthalene diimide conjugated units on its surface after pretreatment, and then prepares it into cellulose-based polyurethane. The cellulose-based gel electrolyte has a strong cross-linking density and a stable structure that is not easily destroyed. The naphthalene diimide conjugated units are introduced into the main chain of the cellulose-based polyurethane. The π-π interaction of the conjugated units will promote electron delocalization, giving the cellulose-based polyurethane electrical activity, thereby improving the electrical properties of the gel electrolyte.

[0047] 4. The present invention deposits a composite metal oxide containing copper oxide and tin oxide on a MXene nanosheet to obtain a composite nanomaterial. The synergistic effect of copper oxide, tin oxide and MXene nanohybrid increases the surface area, conductivity and active sites of the composite nanomaterial, and enhances the electrochemical performance. Furthermore, a sulfonate ion group with ion transport capability is introduced on the surface of the composite nanomaterial through a chemical reaction to obtain a composite modifier, and then the composite modifier is connected to the cellulose-based polyurethane structure by forming a chemical bond, so that the electrical properties of the cellulose-based polyurethane are significantly improved, and the dispersibility of the composite modifier in the cellulose-based polyurethane is improved; in addition, the naphthalene diimide conjugated unit introduced by the modified microcrystalline cellulose can passivate the oxygen defects of the composite metal oxide in the composite nanomaterial, improve the conductivity of the composite metal oxide, and thus further improve the conductivity of the gel electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 It is a process flow chart of the preparation method of the solar cell gel electrolyte of the present invention;

[0049] Figure 2 It is a comparison chart of the conductivity test results of the solar cell gel electrolytes prepared in Examples 2-4 of the present invention and Comparative Examples 1-7;

[0050] Figure 3 It is a comparison chart of the test results of photoelectric conversion efficiency of dye-sensitized solar cells formed by assembling the solar cell gel electrolytes prepared in Examples 2-4 of the present invention and Comparative Examples 1-7. DETAILED DESCRIPTION

[0051] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0052] Example 1

[0053] This embodiment discloses a method for preparing a quaternary ammonium salt compound, comprising the following steps:

[0054] Step S1, 3 g of lauric acid, 85 g of acetone, and 0.07 g of tetrabutylammonium bromide were mixed, and ultrasonic treatment was performed for 30 min, and then 12 g of glycidoxypropyl-terminated polydimethylsiloxane was added dropwise at a rate of 1 mL / min, and the temperature was raised to reflux, and the reaction was stirred for 2.5 h. After the reaction was completed, the mixture was filtered, and the obtained crude product was washed 4 times with acetone and dried to obtain an intermediate product A;

[0055] Step S2, adding 4.5 g of intermediate product A to 65 g of toluene, stirring for 30 min, then adding 3 g of tris(3-aminopropyl)amine, stirring at 80° C. and 200 r / min for 25 h, after the reaction, removing the solvent by vacuum rotary evaporation at 70° C., washing the obtained crude product with methanol 7 times, and drying to obtain intermediate product B;

[0056] Step S3, in a nitrogen atmosphere, 2.5 g of iodopropane and 7.5 g of intermediate product B were mixed at 2° C. for 60 min, and then stirred at 60° C. at a speed of 200 r / min for 25 h. The obtained product was precipitated in ether for 36 h, filtered, and vacuum dried at 50° C. for 25 h to obtain a quaternary ammonium salt compound.

[0057] Example 2

[0058] This embodiment discloses a method for preparing a solar cell gel electrolyte, comprising the following steps:

[0059] Step (1), adding tin chloride pentahydrate and copper sulfate pentahydrate into deionized water to form a mixed salt solution, wherein the content of tin ions and copper ions in the mixed salt solution is 40wt%, and at 20°C, under a stirring condition of 150r / min, a sodium hydroxide aqueous solution with a concentration of 1 mol / L is added dropwise to the mixed salt solution at a rate of 0.5mL / min, the temperature is raised to 120°C and the reaction is maintained for 25h, filtered, washed, and a composite metal oxide is obtained, wherein the volume ratio of the mixed salt solution to the sodium hydroxide aqueous solution is 1:0.5;

[0060] Step (2), at room temperature, 2 g of MAX phase Ti 3 AlC 2 The powder was added to 40 mL of 48 wt% hydrofluoric acid within 10 min, stirred for 20 min, and then stirred in an oil bath at 40 ° C for 15 h. After the reaction, centrifuged, and the obtained precipitate was washed with deionized water until the pH of the washing liquid was 5, and then dried at 60 ° C for 16 h to obtain MXene powder;

[0061] The composite metal oxide was added to deionized water, stirred for 1.5 hours, and then MXene powder was added, ultrasonically treated for 30 minutes, filtered, and the obtained solid product was heated at 100°C for 12 hours to obtain a composite nanomaterial, wherein the mass ratio of the composite metal oxide, MXene powder and deionized water was 0.2:1:50;

[0062] Step (3), adding 0.1 g of γ-aminopropyltriethoxysilane to 8 g of an ethanol aqueous solution with a volume fraction of 90%, adjusting the pH to 3 with an acetic acid aqueous solution with a concentration of 0.1 mol / L, and then adding 2 g of the composite nanomaterial, stirring at 60° C. and 400 r / min for 20 min, filtering, washing, and drying to obtain a surface-modified composite nanomaterial;

[0063] 1.5 g of 3,4-dihydroxyphenylacetic acid was dissolved in 80 g of N,N-dimethylformamide, and then 1.8 g of 1,3-dicyclohexylcarbodiimide and 1.1 g of N-hydroxysuccinimide were added, and the mixture was stirred for 2 h. Under stirring, 2 g of the surface-modified composite nanomaterial was added, and the pH value was adjusted to 5.4 with a 1 mol / L hydrochloric acid aqueous solution. The mixture was reacted in nitrogen for 20 h, filtered, washed with methanol, and dried to obtain a modified composite nanomaterial;

[0064] 300 g of dimethyl sulfoxide and 0.7 g of sodium hydride were mixed, and after nitrogen was passed through, the mixture was stirred at 20° C. for 20 min, and then the temperature was raised to 70° C. and stirred until the sodium hydride was completely dissolved. The mixture was cooled to room temperature, 4.8 g of the modified composite nanomaterial was added, and the mixture was stirred at 28° C. for 40 min. Then, 2.9 g of 1,3-propane sultone was added, and the reaction was continued by stirring for 4 h. The mixture was filtered, washed, and dried to obtain a composite modifier.

[0065] Step (4), adding 10 g of microcrystalline cellulose to 200 g of N,N-dimethylacetamide and ultrasonicating for 1 hour, cooling and precipitating, repeatedly washing with deionized water and anhydrous ethanol for 8 times, and then vacuum drying at 50° C. to obtain pretreated microcrystalline cellulose;

[0066] 10 g of pretreated microcrystalline cellulose and 0.1 g of p-toluenesulfonic acid were added to 100 g of 5 wt% naphthalene diimide-N,N'-diacetic acid in acetone, and reacted at 120° C. for 8 h. After the reaction was completed, the mixture was centrifuged, washed, and dried to obtain modified microcrystalline cellulose;

[0067] Step (5), mixing NaI and iodine in a light-proof condition, fixing the volume with a solvent of 1,4-butyrolactone, ultrasonicating for 2 hours, sealing and storing in a light-proof condition, to obtain an electrolyte; wherein the concentration of NaI in the electrolyte is 0.2 mol / L, and the concentration of iodine is 0.02 mol / L;

[0068] Use 50g 1-propyl-3-methylimidazole iodide as solvent, dehydrate for 3h at a temperature of 100℃ and a vacuum pressure of 0.11KPa, then add 2.5g modified microcrystalline cellulose and 1.5g quaternary ammonium salt compound under nitrogen protection, stir for 2.5h, cool to 50℃, add 10.1g toluene diisocyanate, and when the reactant becomes viscous, quickly add 3.8g electrolyte, stir for 20min, heat to 60℃, add 0.3g composite modifier, stir for 10min, then add 65.7g electrolyte, heat to 75℃ and react for 5h, put the reaction product into a 70℃ oven until it is in a gel state, and obtain a solar cell gel electrolyte.

[0069] Example 3

[0070] This embodiment discloses a method for preparing a solar cell gel electrolyte, comprising the following steps:

[0071] Step (1), adding tin chloride pentahydrate and copper sulfate pentahydrate into deionized water to form a mixed salt solution, wherein the content of tin ions and copper ions in the mixed salt solution is 50wt%, and adding a 2mol / L sodium hydroxide aqueous solution to the mixed salt solution at a rate of 1.5mL / min under a stirring condition of 250r / min at 40°C, heating to 140°C and maintaining the reaction for 15h, filtering, washing, and obtaining a composite metal oxide, wherein the volume ratio of the mixed salt solution to the sodium hydroxide aqueous solution is 1:2;

[0072] Step (2), at room temperature, 4 g of MAX phase Ti 3 AlC 2 The powder was added to 100 mL of 48 wt% hydrofluoric acid within 20 min, stirred for 40 min, and then stirred in an oil bath at 60 ° C for 12 h. After the reaction, it was centrifuged, and the obtained precipitate was washed with deionized water until the pH of the washing liquid was 6, and then dried at 100 ° C for 10 h to obtain MXene powder;

[0073] The composite metal oxide was added into deionized water, stirred for 2.5 hours, and then MXene powder was added, ultrasonically treated for 60 minutes, filtered, and the obtained solid product was heated at 120°C for 8 hours to obtain a composite nanomaterial, wherein the mass ratio of the composite metal oxide, MXene powder and deionized water was 0.6:1:100;

[0074] Step (3), adding 0.4 g of γ-aminopropyltriethoxysilane to 10 g of an ethanol aqueous solution with a volume fraction of 90%, adjusting the pH to 4 with an acetic acid aqueous solution with a concentration of 0.1 mol / L, and then adding 5 g of the composite nanomaterial, stirring at 70° C. and 400 r / min for 20 min, filtering, washing, and drying to obtain a surface-modified composite nanomaterial;

[0075] 3 g of 3,4-dihydroxyphenylacetic acid was dissolved in 120 g of N,N-dimethylformamide, and then 3.7 g of 1,3-dicyclohexylcarbodiimide and 2.2 g of N-hydroxysuccinimide were added, and the mixture was stirred for 3 h. Then 4 g of the surface-modified composite nanomaterial was added under stirring, and the pH value was adjusted to 5.6 with a 1 mol / L hydrochloric acid aqueous solution. The mixture was reacted in nitrogen for 30 h, filtered, washed with methanol, and dried to obtain a modified composite nanomaterial.

[0076] 500 g of dimethyl sulfoxide and 0.8 g of sodium hydride were mixed, nitrogen was passed through, and the mixture was stirred at 25° C. for 20 min, then the mixture was heated to 80° C. and stirred until the sodium hydride was completely dissolved, then the mixture was cooled to room temperature, 7.4 g of the modified composite nanomaterial was added, and the mixture was stirred at 33° C. for 20 min, and then 5 g of 1,3-propane sultone was added, the mixture was stirred and reacted for 10 h, and then the mixture was filtered, washed, and dried to obtain a composite modifier;

[0077] Step (4), adding 20 g of microcrystalline cellulose to 300 g of N,N-dimethylacetamide and ultrasonicating for 2 h, cooling and precipitating, repeatedly washing with deionized water and anhydrous ethanol for 10 times, and then vacuum drying at 70° C. to obtain pretreated microcrystalline cellulose;

[0078] 15 g of pretreated microcrystalline cellulose and 0.3 g of p-toluenesulfonic acid were added to 200 g of 10 wt % naphthalene diimide-N,N'-diacetic acid in acetone, and reacted at 150° C. for 4 h. After the reaction was completed, the mixture was centrifuged, washed, and dried to obtain modified microcrystalline cellulose;

[0079] Step (5), mixing NaI and iodine in a light-proof condition, fixing the volume with solvent 1,4-butyrolactone, ultrasonicating for 3 hours, sealing and storing in a light-proof condition, to obtain an electrolyte; wherein the concentration of NaI in the electrolyte is 0.8 mol / L, and the concentration of iodine is 0.08 mol / L;

[0080] 100 g of 1-propyl-3-methylimidazolium iodide was used as a solvent, and dehydrated for 1 h at a temperature of 120 ° C and a vacuum pressure of 0.13 KPa. Then, under nitrogen protection, 5 g of modified microcrystalline cellulose and 3.5 g of quaternary ammonium salt compound were added, stirred for 3.5 h, cooled to 55 ° C, and 20.2 g of toluene diisocyanate were added. When the reactant became viscous, 8.1 g of electrolyte was quickly added, stirred for 30 min, heated to 65 ° C, 1 g of composite modifier was added, stirred for 20 min, and then 138.3 g of electrolyte was added. The temperature was raised to 80 ° C and reacted for 5 h. The reaction product was placed in an oven at 80 ° C until it was in a gel state to obtain a solar cell gel electrolyte.

[0081] Example 4

[0082] This embodiment discloses a method for preparing a solar cell gel electrolyte, comprising the following steps:

[0083] Step (1), adding tin chloride pentahydrate and copper sulfate pentahydrate into deionized water to form a mixed salt solution, wherein the content of tin ions and copper ions in the mixed salt solution is 45wt%, and adding a 1.5mol / L sodium hydroxide aqueous solution to the mixed salt solution at a rate of 1mL / min at 30°C and under a stirring condition of 200r / min, heating to 130°C and maintaining the reaction for 20h, filtering, washing, and obtaining a composite metal oxide, wherein the volume ratio of the mixed salt solution to the sodium hydroxide aqueous solution is 1:1.3;

[0084] Step (2), at room temperature, 3 g of MAX phase Ti 3 AlC 2 The powder was added to 70 mL of 48 wt% hydrofluoric acid within 15 min, stirred for 30 min, and then stirred in an oil bath at 50 ° C for 14 h. After the reaction, centrifugation was performed, and the obtained precipitate was washed with deionized water until the pH of the washing liquid was 5.5, and then dried at 80 ° C for 13 h to obtain MXene powder;

[0085] The composite metal oxide was added to deionized water, stirred for 2 hours, and then MXene powder was added, ultrasonically treated for 45 minutes, filtered, and the obtained solid product was heated at 110° C. for 10 hours to obtain a composite nanomaterial, wherein the mass ratio of the composite metal oxide, MXene powder and deionized water was 0.4:1:75;

[0086] Step (3), adding 0.3 g of γ-aminopropyltriethoxysilane to 9 g of an ethanol aqueous solution with a volume fraction of 90%, adjusting the pH to 3.5 with an acetic acid aqueous solution with a concentration of 0.1 mol / L, and then adding 3.5 g of the composite nanomaterial, stirring at 65° C. and a speed of 500 r / min for 30 min, filtering, washing, and drying to obtain a surface-modified composite nanomaterial;

[0087] 2.3 g of 3,4-dihydroxyphenylacetic acid was dissolved in 100 g of N,N-dimethylformamide, and then 2.8 g of 1,3-dicyclohexylcarbodiimide and 1.6 g of N-hydroxysuccinimide were added, and the mixture was stirred for 2.5 h. 3 g of the surface-modified composite nanomaterial was added under stirring, and the pH value was adjusted to 5.5 with a 1 mol / L hydrochloric acid aqueous solution, and the mixture was reacted in nitrogen for 25 h, filtered, washed with methanol, and dried to obtain a modified composite nanomaterial;

[0088] 400 g of dimethyl sulfoxide and 0.75 g of sodium hydride were mixed, and after nitrogen was passed through, the mixture was stirred at 23° C. for 30 min, and then the mixture was heated to 75° C. and stirred until the sodium hydride was completely dissolved. The mixture was cooled to room temperature, and 6.1 g of the modified composite nanomaterial was added, and the mixture was stirred at 30° C. for 30 min. Then 4 g of 1,3-propane sultone was added, and the mixture was stirred for 7 h. The mixture was filtered, washed, and dried to obtain a composite modifier.

[0089] Step (4), adding 15 g of microcrystalline cellulose to 250 g of N,N-dimethylacetamide, ultrasonicating for 1.5 h, cooling and precipitating, repeatedly washing with deionized water and anhydrous ethanol for 9 times, and then vacuum drying at 60° C. to obtain pretreated microcrystalline cellulose;

[0090] 12.5 g of pretreated microcrystalline cellulose and 0.2 g of p-toluenesulfonic acid were added to 150 g of 7.5 wt % naphthalene diimide-N,N'-diacetic acid in acetone, and the mixture was reacted at 135° C. for 6 h. After the reaction was completed, the mixture was centrifuged, washed, and dried to obtain modified microcrystalline cellulose;

[0091] Step (5), mixing NaI and iodine in a light-proof condition, fixing the volume with solvent 1,4-butyrolactone, ultrasonicating for 2.5 hours, sealing and storing in a light-proof condition, to obtain an electrolyte; wherein the concentration of NaI in the electrolyte is 0.5 mol / L, and the concentration of iodine is 0.05 mol / L;

[0092] Use 75g of 1-propyl-3-methylimidazole iodide as solvent, dehydrate for 2h at a temperature of 110°C and a vacuum pressure of 0.12KPa, then add 3.8g of modified microcrystalline cellulose and 2.5g of quaternary ammonium salt compound under nitrogen protection, stir for 3h, cool to 58°C, add 15.6g of toluene diisocyanate, and when the reactant becomes viscous, quickly add 6g of electrolyte, stir for 25min, heat to 63°C, add 0.7g of composite modifier, stir for 15min, then add 102g of electrolyte, heat to 78°C and react for 4.5h, put the reaction product into a 75°C oven until it is in a gel state, and obtain a solar cell gel electrolyte.

[0093] The quaternary ammonium salt compound in the above Examples 2-4 adopts the quaternary ammonium salt compound prepared in Example 1.

[0094] Comparative Example 1

[0095] Comparative Example 1 Compared with Example 4, in the process of preparing the solar cell gel electrolyte in Comparative Example 1, the intermediate product B is used to replace the quaternary ammonium salt compound, and other conditions remain unchanged.

[0096] Comparative Example 2

[0097] Comparative Example 2 Compared with Example 4, in the process of preparing the solar cell gel electrolyte in Comparative Example 2, no quaternary ammonium salt compound was added, and other conditions remained unchanged.

[0098] Comparative Example 3

[0099] Comparative Example 3 Compared with Example 4, in the process of preparing the surface-modified composite nanomaterial, Comparative Example 3 uses MXene powder instead of the composite nanomaterial, and other conditions remain unchanged.

[0100] Comparative Example 4

[0101] Comparative Example 4 Compared with Example 4, in the process of preparing the surface-modified composite nanomaterial, the composite metal oxide is used instead of the composite nanomaterial, and other conditions remain unchanged.

[0102] Comparative Example 5

[0103] Comparative Example 5 Compared with Example 4, in the process of preparing the solar cell gel electrolyte in Comparative Example 5, the modified composite nanomaterial is used instead of the composite modifier, and other conditions remain unchanged.

[0104] Comparative Example 6

[0105] Comparative Example 6 Compared with Example 4, in the process of preparing the solar cell gel electrolyte in Comparative Example 6, no composite modifier was added, and other conditions remained unchanged.

[0106] Comparative Example 7

[0107] Comparative Example 7 Compared with Example 4, in the process of preparing the solar cell gel electrolyte in Comparative Example 7, pretreated microcrystalline cellulose was used instead of modified microcrystalline cellulose, and other conditions remained unchanged.

[0108] In the above examples and comparative examples, hydroxy-1,2-oxathiacyclohexane 2,2-dioxide, CAS No.: 10200-48-3, purity: 98%, is from Zhuocui New Materials Technology (Shanghai) Co., Ltd.; MAX phase Ti 3 AlC 2 Powder, CAS number: 196506-01-1, appearance: powder, active ingredient content: 99.5%, particle size / mesh: 2000 mesh, from Nangong Jiuxin New Material Technology Co., Ltd.; glycidoxypropyl-terminated polydimethylsiloxane, molecular weight: 1000, item number: lnb-1723, from Wuhan Lanabai Pharmaceutical Chemical Co., Ltd.; microcrystalline cellulose (MCC), active ingredient content: 99%, particle size: 70-100um, from Xi'an Tianzheng Pharmaceutical Excipients Co., Ltd.; naphthalene diimide-N,N'-diacetic acid, CAS number: 5880-06-8, purity: 95%, from Zhengzhou Huiju Chemical Co., Ltd.

[0109] Experimental example

[0110] 1. Conductivity test: The conductivity of the solar cell gel electrolytes prepared in Examples 2-4 and Comparative Examples 1-7 was tested using a conductivity meter (DDSJ-308A).

[0111] II. Photoelectric performance test: The solar cell gel electrolytes prepared in Examples 2-4 and Comparative Examples 1-7 were assembled to form a dye-sensitized solar cell (DSSC). The assembly method is as follows:

[0112] (1)TiO 2 Sensitization of the photoanode: Weigh a certain amount of N719 dye into a brown light-proof volumetric flask, dilute with anhydrous ethanol, put it into an ultrasonic cleaner for ultrasonic dispersion for 2 h, take it out and seal it to avoid light (the concentration of the dye solution is 5×10 - 4 mol / L). Take TiO 2 The photoanode was cleaned with anhydrous ethanol. After the ethanol on the surface evaporated, the TiO 2 The photoanode is coated with TiO 2 Place it in a beaker with the tip facing up and pour in the prepared dye solution to cover the TiO 2 The photoanode was immersed for 24 hours, then taken out and rinsed with anhydrous ethanol, and stored in a light-proof drying jar after drying.

[0113] (2) DSSC assembly: Take out appropriate amounts of the solar cell gel electrolytes prepared in Examples 2-4 and Comparative Examples 1-7 and apply them on the sensitized TiO 2 For the photoanode, try to ensure that the electrolyte is evenly applied, cover it with the cleaned counter electrode, and then fix it with a clamp or seal it with a sarin film to assemble it into a DSSC.

[0114] Before the test, a standard single-crystal silicon solar cell was used for calibration, and then each group of DSSC samples was connected to the digital source meter instrument. 2 The photoelectric performance of the DSSC sample was tested under the irradiation of a solar simulator. The effective area of ​​the DSSC is 0.36 cm 2 .

[0115] The test results are shown in Table 1:

[0116] Table 1

[0117]

[0118]

[0119] It can be seen from the test results of Table 1 that the solar cell gel electrolyte prepared by Examples 2-4 of the present invention has good electrical conductivity, and using it in a dye-sensitized solar cell can effectively improve the photoelectric conversion efficiency of the cell. From the comparison of Comparative Examples 1-2 and Example 4, it can be seen that the introduction of the quaternary ammonium salt ion structure and the flexible siloxane long chain in the quaternary ammonium salt compound of the present invention can improve the conductivity and flexibility of the gel electrolyte, and the enhanced flexibility enables the solar cell gel electrolyte to better infiltrate the photoanode, reduce the interfacial contact resistance of the solar cell, and improve the photoelectric conversion rate; from the comparison of Comparative Examples 3-4 and Example 4, it can be seen that the composite nanomaterials, copper oxide, tin oxide, and MXene nanohybrids have a synergistic effect, which can improve the conductivity of the composite nanomaterials; from the comparison of Comparative Example 5 and Example 4, it can be seen that the sulfonate ion group with ion transmission ability is introduced on the surface of the composite nanomaterial by chemical reaction, The conductivity of the gel electrolyte can be improved; from the comparison between comparative example 6 and example 4, it can be seen that the composite modifier of the present invention improves the conductivity of the gel electrolyte through the synergistic effect of copper oxide, tin oxide, and MXene nanohybrids and the ion transport effect of the sulfonate ion group; from the comparison between comparative example 7 and example 4, it can be seen that the microcrystalline cellulose is modified and the naphthalene diimide conjugated unit is introduced, which can promote electron delocalization through π-π interaction and give the cellulose-based polyurethane electrical activity on the one hand, and on the other hand, the naphthalene diimide conjugated unit can passivate the oxygen defects of the composite metal oxide in the composite nanomaterial, improve the conductivity of the composite metal oxide, and thus improve the electrical properties of the gel electrolyte.

[0120] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a solar cell gel electrolyte, characterized in that: The following steps are involved: Step (1), using tin chloride pentahydrate and copper sulfate pentahydrate as metal precursors to prepare a composite metal oxide; Step (2), using MAX phase Ti3AlC2 powder as raw material to prepare MXene powder; MXene powder and composite metal oxide are composited to obtain composite nanomaterials; Step (3), the composite nanomaterial is treated with γ-aminopropyltriethoxysilane to obtain a surface-modified composite nanomaterial; the surface-modified composite nanomaterial is reacted with 3,4-dihydroxyphenylacetic acid to obtain a modified composite nanomaterial; the modified composite nanomaterial is reacted with 1,3-propane sultone to obtain a composite modifier; Step (4), the pretreated microcrystalline cellulose is modified by naphthalene diimide-N,N'-diacetic acid to obtain modified microcrystalline cellulose; Step (5), NaI and iodine are mixed, and 1,4-butyrolactone is used as a solvent to obtain an electrolyte; The modified microcrystalline cellulose, quaternary ammonium salt compound, toluene diisocyanate and composite modifier are reacted as raw materials and then mixed with electrolyte to prepare a solar cell gel electrolyte; Wherein, the preparation method of the quaternary ammonium salt compound comprises the following steps: Step S1, lauric acid reacts with glycidoxypropyl-terminated polydimethylsiloxane to obtain an intermediate product A; Step S2, reacting the intermediate product A with tris(3-aminopropyl)amine to obtain an intermediate product B; Step S3, using the intermediate product B and iodopropane as raw materials to prepare a quaternary ammonium salt compound.

2. The method for preparing a solar cell gel electrolyte according to claim 1, characterized in that: In the step (1), the preparation method of the composite metal oxide is as follows: tin chloride pentahydrate and copper sulfate pentahydrate are added to deionized water to form a mixed salt solution, wherein the content of tin ions and copper ions in the mixed salt solution is 40-50wt%, and a sodium hydroxide aqueous solution with a concentration of 1-2 mol / L is added dropwise to the mixed salt solution at a rate of 0.5-1.5 mL / min under the stirring condition of 150-250 r / min at 20-40°C, and the temperature is raised to 120-140°C and the reaction is maintained for 15-25 hours, and the composite metal oxide is filtered and washed to obtain the composite metal oxide, wherein the volume ratio of the mixed salt solution to the sodium hydroxide aqueous solution is 1:(0.5-2).

3. The method for preparing a solar cell gel electrolyte according to claim 1, characterized in that: In the step (2), the preparation method of the composite nanomaterial is: At room temperature, MAX phase Ti3AlC2 powder is added to 48wt% hydrofluoric acid within 10-20min, stirred for 20-40min, and then stirred in an oil bath at 40-60°C for 12-15h. After the reaction is completed, centrifugation is performed, and the obtained precipitate is washed with deionized water until the pH of the washing liquid is 5-6, and then dried at 60-100°C for 10-16h to obtain MXene powder; wherein the amount ratio of MAX phase Ti3AlC2 powder to hydrofluoric acid is (2-4)g:(40-100)mL; The composite metal oxide is added to deionized water, stirred for 1.5-2.5 hours, and then MXene powder is added, ultrasonically treated for 30-60 minutes, filtered, and the obtained solid product is heated at 100-120°C for 8-12 hours to obtain a composite nanomaterial, wherein the mass ratio of the composite metal oxide, MXene powder and deionized water is (0.2-0.6):1:(50-100).

4. The method for preparing a solar cell gel electrolyte according to claim 1, characterized in that: In the step (3), the preparation method of the surface-modified composite nanomaterial is as follows: adding γ-aminopropyltriethoxysilane to an ethanol aqueous solution with a volume fraction of 90%, adjusting the pH to 3-4 with an acetic acid aqueous solution with a concentration of 0.1 mol / L, and then adding the composite nanomaterial, stirring and reacting at 60-70°C and a speed of 400-600 r / min for 20-40 minutes, filtering, washing, and drying to obtain the surface-modified composite nanomaterial; wherein the mass ratio of γ-aminopropyltriethoxysilane, ethanol aqueous solution, and composite nanomaterial is (0.1-0.4):(8-10):(2-5).

5. The method for preparing a solar cell gel electrolyte according to claim 1, characterized in that: In the step (3), the preparation method of the modified composite nanomaterial is as follows: 3,4-dihydroxyphenylacetic acid is dissolved in N,N-dimethylformamide, 1,3-dicyclohexylcarbodiimide and N-hydroxysuccinimide are added, and the mixture is stirred for 2-3 hours. The surface-modified composite nanomaterial is added under stirring, the pH value is adjusted to 5.4-5.6 with a 1 mol / L hydrochloric acid aqueous solution, the mixture is reacted in nitrogen for 20-30 hours, filtered, washed with methanol, and dried to obtain the modified composite nanomaterial; wherein the mass ratio of 3,4-dihydroxyphenylacetic acid, N,N-dimethylformamide, 1,3-dicyclohexylcarbodiimide, N-hydroxysuccinimide, and the surface-modified composite nanomaterial is (1.5-3):(80-120):(1.8-3.7):(1.1-2.2):(2-4).

6. The method for preparing a solar cell gel electrolyte according to claim 1, characterized in that: In the step (3), the preparation method of the composite modifier is as follows: dimethyl sulfoxide and sodium hydride are mixed, nitrogen is passed through, and the mixture is stirred at 20-25°C for 20-40 minutes, then the mixture is heated to 70-80°C and stirred until the sodium hydride is completely dissolved, the mixture is cooled to room temperature, the modified composite nanomaterial is added, the mixture is stirred at 28-33°C for 20-40 minutes, 1,3-propane sultone is added, the reaction is continued with stirring for 4-10 hours, the mixture is filtered, washed, and dried to obtain the composite modifier; wherein the mass ratio of dimethyl sulfoxide, sodium hydride, modified composite nanomaterial, and 1,3-propane sultone is (300-500):(0.7-0.8):(4.8-7.4):(2.9-5).

7. The method for preparing a solar cell gel electrolyte according to claim 1, characterized in that: In the step (4), the preparation method of the modified microcrystalline cellulose comprises: mixing microcrystalline cellulose and N,N-dimethylacetamide in a mass ratio of (10-20):(200-300), ultrasonicating for 1-2 hours, cooling and precipitating, washing, and drying to obtain pretreated microcrystalline cellulose; Pretreated microcrystalline cellulose and p-toluenesulfonic acid are added to an acetone dispersion of 5-10wt% naphthalene diimide-N,N'-diacetic acid, mixed, reacted at 120-150°C for 4-8h, and after the reaction, centrifuged, washed, and dried to obtain modified microcrystalline cellulose; wherein the mass ratio of the pretreated microcrystalline cellulose, p-toluenesulfonic acid, and the acetone dispersion of naphthalene diimide-N,N'-diacetic acid is (10-15):(0.1-0.3):(100-200).

8. The method for preparing a solar cell gel electrolyte according to claim 1, characterized in that: In the step (5), the preparation method of the solar cell gel electrolyte is as follows: NaI and iodine are mixed under light-proof conditions, the volume is fixed with a solvent 1,4-butyrolactone, and after ultrasonic treatment for 2-3 hours, the electrolyte is sealed and stored in a dark place to obtain an electrolyte; wherein the concentration of NaI in the electrolyte is 0.2-0.8 mol / L, and the concentration of iodine is 0.02-0.08 mol / L; Use 1-propyl-3-methylimidazolium iodide as solvent, dehydrate for 1-3 hours at a temperature of 100-120°C and a vacuum pressure of 0.11-0.13KPa, then add modified microcrystalline cellulose and quaternary ammonium salt compounds under nitrogen protection, stir for 2.5-3.5 hours, cool to 50-55°C, add toluene diisocyanate, add electrolyte when the reactant becomes viscous, stir for 20-30 minutes, heat to 60-65°C, add composite modifier, stir for 10-20 minutes, and then add The electrolyte is heated to 75-80°C and reacted for 4-5 hours, and the reaction product is placed in a 70-80°C oven until it is in a gel state to obtain a solar cell gel electrolyte; wherein the mass ratio of 1-propyl-3-methylimidazole iodide, modified microcrystalline cellulose, quaternary ammonium salt compound, toluene diisocyanate, composite modifier, and electrolyte is (50-100):(2.5-5):(1.5-3.5):(10.1-20.2):(0.3-1):(69.5-146.4).

9. The method for preparing a solar cell gel electrolyte according to claim 1, characterized in that: In the step (5), the preparation method of the quaternary ammonium salt compound comprises the following steps: Step S1, mixing lauric acid, acetone and tetrabutylammonium bromide, ultrasonically treating for 20-40 minutes, then dropping glycidoxypropyl-terminated polydimethylsiloxane at a rate of 0.5-1.5 mL / min, heating to reflux, stirring and reacting for 2-3 hours, filtering, washing and drying after the reaction to obtain an intermediate product A; wherein the mass ratio of lauric acid, acetone, tetrabutylammonium bromide and glycidoxypropyl-terminated polydimethylsiloxane is (2-4):(70-100):(0.05-0.1):(8-16); Step S2, adding the intermediate product A to toluene, stirring for 20-40 minutes, then adding tri(3-aminopropyl)amine, stirring at 70-90° C. and at a speed of 150-250 r / min for 20-30 hours, after the reaction is completed, removing the solvent by vacuum rotary evaporation at 60-80° C., washing, and drying to obtain an intermediate product B; wherein the mass ratio of the intermediate product A, toluene, and tri(3-aminopropyl)amine is (3-6):(50-80):(2-4); Step S3, in a nitrogen atmosphere, mixing iodopropane and the intermediate product B at 0-3° C. for 40-80 min, and then stirring at 50-70° C. at a speed of 150-250 r / min for 20-30 h, precipitating the resulting product in ether for 24-48 h, filtering, and drying to obtain a quaternary ammonium salt compound; wherein the mass ratio of iodopropane to the intermediate product B is (1.5-3.5):(5-10).

10. A solar cell gel electrolyte prepared by the method for preparing a solar cell gel electrolyte according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Ion liquid electrolyte containing bi-(fluorosulfonic acid) imines ion and iodine ion, and application thereof

    CN101436467B

  • A solid electrolyte for dye-sensitized solar cells

    CN109545562B